2021
DOI: 10.1177/08258597211034642
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Connection Between Spiritual Transcendence and Quality of Life? A Cross-Sectional Survey Study in Patients Under the End-of-Life Care

Abstract: Background: There is limited data available on the spiritual dimension of palliative care in Eastern Europe. In countries such as Poland, investigating spirituality and its essential aspects is further complicated because in a predominantly Catholic country, spirituality is mistakenly thought to be identical to religiousness. Aim: This study investigated the connection between spiritual transcendence, meaning in life, altruism, and the quality of life of cancer patients in end-of-life care in an Eastern Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Also, spiritual well-being is indirectly significantly related to quality of life through mediation of pain self-efficacy (B = 0.021). Consistent with the results of the present study, the findings of Wysocka et al [ 53 ]; Lee [ 54 ]; Pilger et al [ 28 ]; and Bai and Lazenby [ 55 ], they have shown that there is a significant positive correlation between spiritual well-being and quality of life. In explaining the relationship between spiritual well-being and quality of life, it can be stated that spirituality by creating hope and a sense of meaning in life, can help them cope better in difficult situations and improve their quality of life [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, spiritual well-being is indirectly significantly related to quality of life through mediation of pain self-efficacy (B = 0.021). Consistent with the results of the present study, the findings of Wysocka et al [ 53 ]; Lee [ 54 ]; Pilger et al [ 28 ]; and Bai and Lazenby [ 55 ], they have shown that there is a significant positive correlation between spiritual well-being and quality of life. In explaining the relationship between spiritual well-being and quality of life, it can be stated that spirituality by creating hope and a sense of meaning in life, can help them cope better in difficult situations and improve their quality of life [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Findings of DeMaria et al [ 49 ] in patients with multiple chronic diseases; Costa et al [ 25 ], and Kever et al [ 21 ] in patients with multiple sclerosis; Ren et al [ 50 ] in patients with chronic wounds; Qi et al [ 51 ] in patients with type 2 diabetes; Aydın, and Demir [ 22 ], and Dun et al [ 52 ] in cancer patients; indicate that there is a positive and significant correlation between social support and quality of life. Wysocka et al [ 53 ] have shown that there is relationship between meaning of life, spirituality and quality of life in patients under the end-of-life care. According to researches of; Lee [ 54 ] in patients with lung cancer; Pilger et al [ 28 ] in adults with hemodialysis; higher levels of spiritual well-being is associated with increasing the QOL scores in the physical, psychological, social relationships, and environmental aspects.…”
Section: Introductionmentioning
confidence: 99%